Investigation of Changes in Mechanical Properties and Microstructures of Mild Steel Joint by Oxy-Hydrogen Welding - Ates, H.; Cakır, M.E.; Kurt, A.; Uygur, I.; Turker, M. (Металлофизика и новейшие технологии, 2014)
In this paper, in order to see weldability behaviour of mild steels joint by the oxy-hydrogen welding technique, an investigation of changes in mechanical properties and microstructures of mild steel is carried out. The specimens with 1.5 mm thickness and 125 mm length are welded by using both the oxyhydrogen and oxy-acetylene gases. Microstructural analysis is carried out on the cross sectional area of the welding zone in order to compare the changes in weld metals and the heat affected zones in terms of the welding gases. Experimental results of the tensile strength and microhardness obtained with mechanical tests show that samples welded with oxy-acetylene exhibited 10% higher yield strength than that of the samples welded with oxy-hydrogen. However, the oxy-hydrogen welding technique can be used as an alternative to the oxy-acetylene welding, since it has advantageous of being clean and economic. С целью выяснения качества сварного шва на малоуглеродистой стали, полученного водород-кислородной сваркой, проведено исследование изменений механических свойств и микроструктуры данного типа стали. Образцы толщиной 1,5 мм и длиной 125 мм сваривались как водород-кислородной, так и ацетиленокислородной сваркой. Был проведён микроструктурный анализ поперечного сечения зоны сварки с целью сравнения изменений в металле шва и зоне термического влияния в зависимости от сварочного газа. Экспериментальные результаты по пределу прочности при растяжении и микротвёрдости, полученные при механических испытаниях, показали, что образцы, сваренные ацетиленокислородной сваркой, имеют прочность при растяжении на 10% выше, чем водород-кислородной. Однако водород-кислородная сварка может быть использована как альтернатива ацетиленокислородной сварке, так как она имеет преимущества по чистоте и экономичности. З метою з’ясування якости зварюваного шва на маловуглецевій сталі, виробленого водневокисневим зварюванням, виконано дослідження змін механічних властивостей і мікроструктури даного типу сталі. Зразки товщиною у 1,5 мм та довжиною у 125 мм зварювалися як водневокисневим, так і ацетиленокисневим зварюванням. Виконано мікроструктурну аналізу поперечного перерізу зони зварювання з метою порівняння змін у металі шва та зоні термічного впливу в залежності від зварювального газу. Експериментальні результати стосовно границі міцности при розтягу та мікротвердости, одержані під час механічних випробувань, показали, що зразки, зварені ацетиленокисневим зварюванням, мають міцність при розтягу, на 10% вищу, ніж зварені водневокисневою газовою сумішшю. Однак водневокисневе зварювання може бути використано як альтернатива ацетиленокисневому зварюванню завдяки його перевазі за чистотою та економічністю.